An analysis of business cycle fluctuations in Slovenia and the euro area - Radovan, Jan (knjige, 2023)
This paper aims to analyse business cycle dynamics in Slovenia and the euro area. In order to thoroughly tackle the research topic, several modelling methodologies are proposed. First, the characteristics of contractions and expansions and the question of business cycle synchronization between the two focal economies are investigated through the lens of the most common nonparametric approach. Against this background, the most relevant parametric modelling alternatives are closely considered in order to challenge the findings coming from the non-parametric modelling concepts. Second, an analysis of the duration dependence of the particular phases of the business cycle is presented. By utilizing the most relevant (non-parametric) weak-form and strong-form testing procedures, we find some evidence of positive duration dependence of contractions in the case of Slovenia, and largely inconclusive results for positive duration dependence of expansions in the case of euro area. Lastly, given the potential usefulness of the Markov-switching (MS) modelling concept for the real-time business cycle analysis, we utilize Markov-switching Bayesian dynamic factor model (MS-BDFM) in order to infer the probability of the low growth regime and the probability of current quarter negative growth in Slovenia and the euro area.